2010
DOI: 10.1038/leu.2009.301
|View full text |Cite
|
Sign up to set email alerts
|

FES kinases are required for oncogenic FLT3 signaling

Abstract: The closely related non-receptor tyrosine kinases FEline Sarcoma (FES) and FEs Related (FER) are activated by cell surface receptors in hematopoietic cells. Despite the early description of oncogenic viral forms of fes, v-fes, and v-fps, the implication of FES and FER in human pathology is not known. We have recently shown that FES but not FER is necessary for oncogenic KIT receptor signaling. Here, we report that both FES and FER kinases are activated in primary acute myeloid leukemia (AML) blasts and in AML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…MV4-11, MOLM-13, MOLM-14 and THP-1 cells were treated with each inhibitor at a concentration of 1.0 μM, and apoptosis was assayed as Caspase 3/7 activity three days later. The three Fes inhibitors as well as tandutinib each induced significant apoptosis under these conditions in all three Flt3-ITD + AML cell lines but not in THP-1 cells, consistent with the observation that Fes is constitutively active in Flt3-ITD + AML cells [14] (Fig 3). Both TAE-684 and HG7-92-01 induced a percentage of apoptotic cells equal to or greater than that observed with tandutinib, while the effect of WZ4-49-1 was less pronounced.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…MV4-11, MOLM-13, MOLM-14 and THP-1 cells were treated with each inhibitor at a concentration of 1.0 μM, and apoptosis was assayed as Caspase 3/7 activity three days later. The three Fes inhibitors as well as tandutinib each induced significant apoptosis under these conditions in all three Flt3-ITD + AML cell lines but not in THP-1 cells, consistent with the observation that Fes is constitutively active in Flt3-ITD + AML cells [14] (Fig 3). Both TAE-684 and HG7-92-01 induced a percentage of apoptotic cells equal to or greater than that observed with tandutinib, while the effect of WZ4-49-1 was less pronounced.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, the activity of Flt3-ITD downstream signaling mediators, particularly STAT5 and PI3K, were also substantially decreased in Fes-knockdown cells. Co-immunoprecipitation studies demonstrated that the two kinases physically interact, and knockdown of Flt3-ITD led to a decrease in Fes kinase activity, supporting the idea that Fes is a downstream mediator of Flt3-ITD oncogenic signaling [14]. Finally, treatment of primary AML patient samples with the Flt3 inhibitor, SU5416, reduced both Flt3 and Fes activation.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the transient initial clinical response is followed by the appearance of resistant blasts. Recent efforts to identify alternative targets in FLT3-ITD AML lead to the identification of candidates such as PU.1 [21], NFATc1 [22], SIRT1 [23], PIM [24], FES [25], SYK [26], and BTK [27]. We describe here an essential pathway downstream of FLT3-ITD in AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to date, naturally occurring "gain-of-function" mutations have never been described. Nevertheless, in lymphoid type human cancers, hyper-activation of Fes kinase has proven to be crucial in sustaining the uncontrolled proliferation triggered by constitutively active mutants of membrane receptors, such as the inhibitor-resistant variant of c-Kit, KITD816V (expressed in several neoplasms) [49], and the FLT3 mutants expressed in acute myeloid leukaemia (AML) blasts or in AML cell lines [50].…”
Section: Fes In Cancer Biologymentioning
confidence: 99%